2021
DOI: 10.1111/ejn.15100
|View full text |Cite
|
Sign up to set email alerts
|

Monetary payoffs modulate reciprocity expectations in outcome evaluations: An event‐related potential study

Abstract: Choosing cooperation or aggression relies on reciprocity preferences which refer to the tendency of an individual to return cooperative or aggressive action for cooperative or aggressive action (i.e., positive or negative reciprocity preference). The reciprocity preference is positively correlated with reciprocity expectation, wherein individuals with stronger reciprocity preferences may have higher expectations than future cooperative or aggressive behavior should be delivered by beneficiaries (positive recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Therefore, an-eye-for-an-eye strategy or negative reciprocity belief serves as the missing link elucidating when and why some employees cheat as a result of BLM and others do not. Negative reciprocity is a powerful psychological mechanism which even supersedes positive reciprocity ( Chernyak et al, 2019 ), and it significantly affects individual behavior in situations involving economic outcomes ( Li et al, 2021 ), such as bottom-line-driven work environments. In their meta-analysis on 96,930 individuals from 207 studies, Greco et al (2019) present consistent support for negative reciprocity in explaining why one party shows aggressive behavior (with equal or higher severity and activity) when instigated by negative work behavior from another party in the organization.…”
Section: Theoretical Rationale and Hypothesesmentioning
confidence: 99%
“…Therefore, an-eye-for-an-eye strategy or negative reciprocity belief serves as the missing link elucidating when and why some employees cheat as a result of BLM and others do not. Negative reciprocity is a powerful psychological mechanism which even supersedes positive reciprocity ( Chernyak et al, 2019 ), and it significantly affects individual behavior in situations involving economic outcomes ( Li et al, 2021 ), such as bottom-line-driven work environments. In their meta-analysis on 96,930 individuals from 207 studies, Greco et al (2019) present consistent support for negative reciprocity in explaining why one party shows aggressive behavior (with equal or higher severity and activity) when instigated by negative work behavior from another party in the organization.…”
Section: Theoretical Rationale and Hypothesesmentioning
confidence: 99%
“…Previous studies have proposed the dual‐strategies theory of social hierarchy, which suggests that individuals mainly depend on two types of strategies (i.e., dominance‐based and prestige‐based strategies) to gain a superior status in the social hierarchy (Cheng, 2020 ; McClanahan et al, 2022 ). To be more specific, the dominance‐based strategy involves the use of force or coercion to demand compliance from others, whereas a prestige‐based strategy involves demonstrating capacity based on skills, abilities, knowledge, or task performance in the presence of others so the others admire, respect or approve (Cloutier et al, 2016 ; Feng et al, 2016 ; Henrich & Gil‐White, 2001 ; Li, Krueger, et al, 2021 ; Li, Xu, & Zhong, 2021 ). For example, Zink et al ( 2008 ) established the social hierarchies based on prestige: participants demonstrated the visual‐related skills in a visual discrimination task.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have interpreted FRN as a “negative prediction error” index that is more negative‐going for negative feedback (e.g., reward‐loss or performance error) than for positive feedback (Holroyd et al, 2003 ; Holroyd & Krigolson, 2010 ; Nieuwenhuis et al, 2004 ). Several studies have also reported that the FRN can be regarded as an “expectation violation” signal that codes for expectation violation such that the greater violation of expectations leads to a more negative‐going FRN deflection (Gu et al, 2020 ; Li, Krueger, et al, 2021 ; Li, Xu, & Zhong, 2021 ; Van der Molen et al, 2013 ). Along with the FRN, the other key ERP index reflecting feedback evaluation is P300.…”
Section: Introductionmentioning
confidence: 99%